SANKSI ADAT BATALNYA MELAKSANAKAN PERKAWINAN PADA MASYARAKAT DAYAK DESA (Studi Kasus di Desa Mengkirai Kecamatan Kayan Hilir Kabupaten Sintang) - Gadion SH (Universitas Kapuas Sintang, 2021)
Marriage is a gift from God Almighty as every human desires to find a life partner and build a household until separated by death. In carrying out the marriage, there is a relationship between men and women to come together in family. Hence, in aim to come together between two families, a meeting are needed between the men and women. This meeting are intended to deals with the implementation of the marriage party, annulment of marriage from man or woman which enable to cause a dispute between the two parties. Thus, the recovery must be done by a customary system.In result, the annulment of marriage which performed one-sidedly by both men and women in Dayak Desa community is one of disobedience custom. This is as a responsibility tha must be fulfilled for one party because it has been said as means as “lie” (Ngemula). Customary payments formed as “Tempayan”, 1 (rinti) of pig, a chicken, 4 kl rice (6 kulak), iron (nails), sarong cloth (kain Tapih) for opening words of each party Rp. 50,000,and the embarrassment cover money of Rp 1,000.000. These all customary range must be met by the party who annulled the marriage. The factors are caused to annul a marriage namely, the fear of building a household because there is no mental readiness and for not having a permanent job. Thus, the fear arises at the implementation of the marriage.Based on the conclusions mentioned above, the researcher suggest that range of customs of annulment of a lie marriages (Ngemula) in Mengkirai Desa, Kayan Hilir Subdistrict, Sintang Regency, It must be maintained based on the habits of the Dayak Desa community. Customary administrators in Mengkirai Village, Kayan Hilir Subdistrict, Sintang Regency, it is need to be more improved in socializing disobedience custom in the community. The improvement is needed to reduce the marriage annulment.